Declining global warming effects on the phenology of spring leaf unfolding - Fu, Yongshuo H.; Zhao, Hongfang; Piao, Shilong; Peaucelle, Marc; Peng, Shushi; Zhou, Guiyun; Ciais, Philippe; Huang, Mengtian; Menzel, Annette; Peñuelas, Josep; Song, Yang; Vitasse, Yann; et al. (Nature (London), 2015)
Spring leaf unfolding has been occurring earlier in the year because of rising temperatures; however, long-term evidence in the field from 7 European tree species studied in 1,245 sites shows that this early unfolding effect is being reduced in recent years, possibly because the reducing chilling and/or insolation render trees less responsive to warming. Opposing effects of warming on tree greening Spring leaf unfolding has been occurring earlier in the year because of rising temperatures, but some experimental evidence has suggested that the effect is becoming less marked because trees are not receiving the necessary chilling required to trigger leaf unfolding. Shilong Piao and colleagues present evidence based on long-term field observations of seven European tree species studied in 1,245 locations across Europe confirming that a weakening of temperature sensitivity of leaf unfolding is indeed occurring. The authors provide model-based evidence that the chilling effect is at least partially responsible. Earlier spring leaf unfolding is a frequently observed response of plants to climate warming 1 , 2 , 3 , 4 . Many deciduous tree species require chilling for dormancy release, and warming-related reductions in chilling may counteract the advance of leaf unfolding in response to warming 5 , 6 . Empirical evidence for this, however, is limited to saplings or twigs in climate-controlled chambers 7 , 8 . Using long-term in situ observations of leaf unfolding for seven dominant European tree species at 1,245 sites, here we show that the apparent response of leaf unfolding to climate warming (S T , expressed in days advance of leaf unfolding per °C warming) has significantly decreased from 1980 to 2013 in all monitored tree species. Averaged across all species and sites, S T decreased by 40% from 4.0 ± 1.8 days °C −1 during 1980–1994 to 2.3 ± 1.6 days °C −1 during 1999–2013. The declining S T was also simulated by chilling-based phenology models, albeit with a weaker decline (24–30%) than observed in situ . The reduction in S T is likely to be partly attributable to reduced chilling. Nonetheless, other mechanisms may also have a role, such as ‘photoperiod limitation’ mechanisms that may become ultimately limiting when leaf unfolding dates occur too early in the season. Our results provide empirical evidence for a declining S T , but also suggest that the predicted strong winter warming in the future may further reduce S T and therefore result in a slowdown in the advance of tree spring phenology.